Penerapan Model Pembelajaran Aktif Tipe Group to Group Exchange (GGE) dalam Meningkatkan Hasil Belajar Siswa pada Materi Hidrokarbon Kelas X SMA Negeri 10 Pekanbaru - Edi Kurniawan; Rahmiza Dewi (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2019)
Abstract This research aims to find out the increase student learning outcomes on the subject of hidrocarbon with the application of active learning type of Group to Group Exchange (GGE) of grade X at Senior High School 10 Pekanbaru. This type of research is experimental research with data retrieval time from the date of 18 May to 1 June 2013. The samples in this research are students of class X2 as experimental class and class X1 as control class selected after conducting test of homogeneity. Techniques of data collection in this research was to test the homogeneity as initial data on the material previously, documentation, observations, pretest and posttest as final data. Final data analysis in this research using test "t". From the calculations, t count = 4.59 at significant level of 5% obtained t table = 1.66, showing that t count≥ t table so that Ho is rejected and Ha accepted. The magnitude of the average normalized gain <N-GAIN> student learning outcomes experimental class was 0.75 which includes high category, and for the control class is 0.70 which included a middle category. Based on the results of these data analysis, it is concluded that an increase in learning outcomes on the subject of hidrocarbon with the application of active learning type of Group to Group Exchange (GGE) of grade X at Senior High School 10 Pekanbaru. Keywords : Active Learning Model, Group to Group Exchange (GGE), Learning Outcomes, Hidrocarbon